Pengaruh Penambahan Ekstrak Bunga Rosella (Hibiscus sabdariffa Linn) terhadap Keasaman pada Yogurt (pH) - Muh. Hasir Adam (JURNAL PETERNAKAN LOKAL, 2019)
The study aims to determine the extent of the influence of the addition of roselle flower extract in the process of making yogurt and the addition of an optimal level to obtain a quality yogurt products. The research was conducted in August-September 2011 in the Laboratory of Livestock Product Technology and Basic Animal Nutrition Faculty of Animal Husbandry Hasanuddin University, Makassar. The material used was fresh milk, rosella flower extract, plain starter yogurt (Lactobacillus bulgaricus and Streptococcus thermophilus), 1% NaOH, 96% ethanol, packing materials, aluminum foil, paper labels, aquades, and alcohol 75%. The equipment used is oven, mixer, filters, stoves, pots, basins, thermometer, jars, burette, plastic wrap, analytical balance, the titration, the volume pipettes, pipette drops, pipette man, measuring cup, glass cup, erlenmeyer, pH meters . Experimental design used in this study was Complete Randomized Design (CRD) with a pattern of 2 x 4 factorial with five replications. Factor A Long incubation (A1 = 12 hours at 30oC) and (A2 = 16 hours at 30oC). Factor B Giving Rosella Flower Extract (B1 = 0% Extracts rosella flowers, B2 = 0.5% roselle flower extract, B3 = 1% rosella flower extract, and B4 = 1.5% roselle flower extract). The observed parameters namely pH. The results showed higher levels of rosella flower extract the higher acidity of the yogurt with an average pH of 3.5. Storage of up to 16 hours showed no decrease in quality of yogurt.